2021
DOI: 10.3389/fonc.2021.766181
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study: How to Identify High-Risk T1–2 Esophageal Cancer Patients?

Abstract: BackgroundDue to individualized conditions of lymph node metastasis (LNM) and distant metastasis (DM), the following therapeutic strategy and diagnosis of T1–2 esophageal cancer (ESCA) patients are varied. A prediction model for identifying risk factors for LNM, DM, and overall survival (OS) of high-risk T1–2 ESCA patients is of great significance to clinical practice.MethodsA total of 1,747 T1–2 ESCA patients screened from the surveillance, epidemiology, and end results (SEER) database were retrospectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These indicated that our model was superior to the FIGO stage, providing greater net clinical benefit with a threshold probability between 0 and 90%. CIC analysis ( Figure 6 ) was performed to evaluate the clinical applicability of the risk prediction nomograms ( 18 , 19 ) and FIGO stage. The DCA and CICs showed that the nomograms had greater net benefit within wide and practical ranges of threshold probabilities and impacted patient outcomes, indicating that our models have a significant predictive value.…”
Section: Resultsmentioning
confidence: 99%
“…These indicated that our model was superior to the FIGO stage, providing greater net clinical benefit with a threshold probability between 0 and 90%. CIC analysis ( Figure 6 ) was performed to evaluate the clinical applicability of the risk prediction nomograms ( 18 , 19 ) and FIGO stage. The DCA and CICs showed that the nomograms had greater net benefit within wide and practical ranges of threshold probabilities and impacted patient outcomes, indicating that our models have a significant predictive value.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the most commonly used methods for preoperative staging of esophageal cancer mainly include computed tomography (CT), endoscopic ultrasonography (EUS) and positron emission tomography (PET) (16)(17)(18)(19)(20)(21). Among them, CT, especially enhanced CT, is the most commonly used examination method to exclude distant metastasis of esophageal cancer patients, which can accurately find the most common liver, brain and lung metastasis (21,22).…”
Section: Introductionmentioning
confidence: 99%